Musealisation of folk art - on the occasion of the 100th anniversary of the Ethnographic Museum - Rittig Šiško, Tea (Array, 2019)
Starting from the concept of folk art as a historical phenomenon that refers to par- ticular civic processes of valorisation, selection and representation of peasant painting traditions, its role can be considered against the backdrop of specific economic, social and political circumstances of congenial cultural activities, which, from the end of the 19th century to the World War II, included the practices of gathering of ethnographic collections, the formation of the first museum collections and museum activities, the development of artistic crafts, encouragement of home-based handicraft businesses, as well as education in visual arts through professional education. This paper provides a historical overview of the process of affirmation of folk art, with an emphasis on musealisation and it is intended as a contribution to the interpretation of the initial collections of the Ethnographic Museum.